SYLLABUS DESIGN - Teti Sumarni; Yuyun Taufik, S.Pd., M.Si. (TEMATIK, 2016)
Abstract : Curriculum is designed to be the guidelines for lecturers to provide clearer, achievable, and measurable teaching goals. Instructions in a good curriculum should be effective. Students require a suitable curriculum for what they need to learn and for characteristics they have. This research applies qualitative methods with descriptive case study as its framework, to analyze the syllabus of an English Course in Politeknik LP3I Bandung called English for Specific Purposes One: English for Job Seekers. The theories adapted from Hunkins and Allan (2009), Posner (1992), Johnson (1989), Nunan (1988), and McGrath (2002) and Richard (2001). The data were gained from document analysis and interview. The result of the analysis showed that the syllabus of the course has partially met all required aspects expected to meet students’ characteristics and to fulfill the characteristic of quality syllabuses that would enable students to achieve maximum learning achievement. This situation indicates that the syllabus in need of further improvement.